Microbial Spectra, Physiological Response and Bioremediation Potential of Phragmites australis for Agricultural Production - Kalu, Chimdi Mang; Rauwane, Molemi Evelyn; Ntushelo, Khayalethu (Frontiers in Sustainable Food Systems, 2021)
Common reed (Phragmites australis) can invade and dominate in its natural habitat which is mainly wetlands. It can tolerate harsh environments as well as remediate polluted and environmental degraded sites such as mine dumps and other polluted wastelands. For this reason, this can be a very critical reed to reclaim wastelands for agricultural use to ensure sustainability. The present review manuscript examined the microbial spectra of P. australis as recorded in various recent studies, its physiological response when growing under stress as well as complementation between rhizosphere microbes and physiological responses which result in plant growth promotion in the process of phytoremediation. Microbes associated with P. australis include Proteobacteria, Bacteriodetes, and Firmicutes, Fusobacteria, Actinobacteria, and Planctomycetes families of bacteria among others. Some of these microbes and arbuscular mycorrhizal fungi have facilitated plant growth and phytoremediation by P. australis. This is worthwhile considering that there are vast areas of polluted and wasted land which require reclamation for agricultural use. Common reed with its associated rhizosphere microbes can be utilized in these land reclamation efforts. This present study suggests further work to identify microbes which when administered to P. australis can stimulate its growth in polluted environments and help in land reclamation efforts for agricultural use.